EDITORIAL - Cherulli Marçal, Alexanadre; de Freitas de Mello Junior, Alexandre; Ferreira Marques Neto, Antonio; Rocha Machado, Bianca; Mohamed Radwan Omar Osman, Elzahrã; Castelo Branco Medeiros, Felipe; Tavares Borges, Gabriela; Mendes Junior, Gilmar Jorge; Noleto Ferreira, Lennon Pedro; de Almeida Freitas, Maria Helena; et al. (PÓLEMOS – Revista de Estudantes de Filosofia da Universidade de Brasília, 2013)
Editorial do volume 01, número 02, ano 2012.